The Social Reality of Japanese Society in Rei Kimura's Novel Butterfly in The Wind - Ade Iriani; Hamzon Situmorang; T. Tyrhaya Zein (Madah: Jurnal Bahasa dan Sastra, 2021)
This study is a literary study that discusses the picture of the social reality of Japanese society in a novel by Rei Kimura entitled Butterfly in the Wind. The  method used is descriptive analytic. The data are in the form of excerpts or sentence excerpts in novels that describe the social reality of Japanese society. The theory used is the sociological theory of literature and Marx's social analysis approach. From the analysis, it is concluded that various social realities of Japanese society are depicted in the novel Butterfly in the Wind which includes aspects of politics, economy, culture, education, family, morals, gender, religion, and technology. In the political aspect, it is illustrated that the attitude of government (bakufu) is arbitrary and unfair, especially among farmers and fishermen groups. The economic aspect illustrates the economic gap between groups of aristocrats and ordinary people. Cultural and religious aspects are reflected in the patriarchal culture of Japanese society and Buddhist rituals which are carried out such as funeral processions. The aspect of education illustrates the unfairness and distribution of education for Japanese society at that time. The family aspect shows a picture of affection between family members, especially parents and children. The moral aspect is reflected in the behavior of people who hate Okichi's background as a concubine. The gender aspect illustrates the gender bias between men and women. Finally, on the technological aspect, the reality of Japanese technology is still low compared to European and American countries.